A Dynamic Model for Frequency Response Optimization in Photovoltaic Visible Light Communication - Chen, Shuyan; Yu, Hui; Zhao, Ni; Chen, Lian-Kuan (Journal of lightwave technology, 2023)
Photovoltaic (PV) modules are recently employed in photovoltaic visible light communication (PVLC) for simultaneous energy harvesting and visible light communication. A PV-based receiver features a large signal output, easy optical alignment, and self-powered operation. However, the conventional PVLC model fails to accurately capture the factors affecting the PV module's frequency response. In this paper, we systematically investigate the internal impedance dynamic of PV modules and how that affects PV frequency response under different illuminances. We propose a simplified yet accurate dynamic AC model for PV detection to capture the frequency response characteristics of a self-powered PV module. The proposed model is validated with the impedance spectroscopy characterization methodologies. Experimental results show that a PV module's internal resistance and capacitance depend on incident illuminance, affecting PV's frequency response. The bandwidth is exacerbated under indoor environments with low illuminance levels due to the increased internal resistance of PV modules. We show that adjusting the forward bias conditions can simultaneously reduce the resistance and capacitance values. With the optimization of equivalent trans-impedance based on our proposed model, the data rate of a Cadmium telluride (CdTe) PV module achieves a 3.8 times enhancement under a home scenario illuminance (200 lux). We also demonstrate that the bit error rate (BER) of a 5-Mbits eight-level pulse amplitude modulation (PAM8) signal can be reduced from 9.810 -2 to 1.410 -3 by maximizing the transimpedance gain-bandwidth product. Besides frequency response optimization, the dynamic model is also valuable when investigating other issues in PVLC, such as PV shading and PV layout optimization.